(untitled) (Лучшие интеллектуальные исследования, 2025)
Abstract: the use of pedagogical technologies in teaching English has become an integral part of the modern educational process. Today, the use of innovative approaches and modern technologies in the field of Education makes it possible to make the educational process more effective and interesting. Pedagogical technologies allow teachers to improve the learning process of students, increase their interest and raise the level of their assimilation.